DEVELOPMENT OF USER TRUSWORTHINESS MODEL IN TWITTER AND DEVELOPMENT OF INSTITUT TEKNOLOGI BANDUNG SOCIAL NETWORK ANALYSIS APPLICATION - Handayani Sumantri, Isabella
There are many dangers in trusting misinformation. There's a need to filter trusted and untrusted information to avoid these dangers. One way to trust a piece of information is by checking the trustworthiness of the bearer of the information. Based on this background, a user trustworthiness model was developed. The SNA ITB application is a social network analysis developed by the SNA ITB team. In this capstone final thesis, some features were added to enhance the application capabilities. Furthermore, bugs and defects found in the application were fixed. User trusworthiness model was built by experimenting on some machine learning architecture combination. Based on the experiment, the model with best performance is the model which use CatBoost algorthim with standard scaling. The model has f1-score of 0.9877. The development of SNA ITB application used FastAPI, Celery, and PostgreSQL in the backend. It also used Vue.JS for the frontend. The result of application development is tested through functional testing, unit testing, and user acceptance testing.